Routledge readings on law and social justice: dispossessions, marginalities, rights - Kannabirān, Kalpana (Routledge readings, 2022)
Routledge Readings on Law and Social Justice: Dispossessions, Marginalities, Rights presents some of the finest essays on social justice, rights and public policy. With a lucid new Introduction, it covers a vast range of issues and offers a compelling guide to understanding law and socio- legal studies in South Asia. The book covers critical themes such as the jurisprudence of rights, justice, dignity, with a focus on the regimes of patriarchy, labour and dispossession. The fourteen chapters in the volume, divided into three sections, examine contested sites of the constitution, courts, prisons, land and complex processes of migration, trafficking, digital technology regimes, geographical indications and their entanglements. This multidisciplinary volume foregrounds the politics and plural lives of/ in law by including perspectives from major authors who have contributed to the academic and/ or policy discourse of the subject. This book will be useful to students, scholars, policymakers and practitioners interested in a nuanced understanding of law, especially those studying law, marginality and violence. It will serve as essential reading for those in law, socio- legal studies, legal history, South Asian studies, human rights, jurisprudence and constitutional studies, gender studies, history, politics, conflict and peace studies, sociology and social anthropology. It will also appeal to legal historians and practitioners of law, and those in public administration, development studies, environmental studies, migration studies, cultural studies, labour studies and economics.